2014
DOI: 10.1155/2014/429761
|View full text |Cite
|
Sign up to set email alerts
|

Status of the Gastric Mucosa with Endoscopically Diagnosed Gastrointestinal Stromal Tumor

Abstract: Background. Since gastrointestinal stromal tumor (GIST) is a mesenchymal submucosal tumor, the endosonographic, CT, and MRI features of gastric GISTs have been widely investigated. However, the GIST-bearing gastric mucosa status has not been reported. Objective. To characterize the GIST-bearing gastric mucosa status in terms of the degree of inflammation and atrophy, assessed endoscopically. Subjects and Methods. The subjects were 46 patients with submucosal tumors (histologically proven gastric GISTs) who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…However, no such association was noted in univariate analysis. Consistent with our results, Nonaka, et al also reported, in 46 patients with gastric GISTs, that the most common mucosal characteristics are non-atrophic, H. pylori negative or mild-atrophic H. pylori positive gastritis [28]. This study demonstrated that the gastric mucosa lying above the GISTs is usually relatively healthy.…”
Section: Discussionsupporting
confidence: 92%
“…However, no such association was noted in univariate analysis. Consistent with our results, Nonaka, et al also reported, in 46 patients with gastric GISTs, that the most common mucosal characteristics are non-atrophic, H. pylori negative or mild-atrophic H. pylori positive gastritis [28]. This study demonstrated that the gastric mucosa lying above the GISTs is usually relatively healthy.…”
Section: Discussionsupporting
confidence: 92%
“…AGML remains an important clinical problem because many people are affected by this condition, which may also cause gastrointestinal bleeding [1, 5]. Previous results have shown that gastric mocosal lesions are associated with gastrointestinal stromal tumors and gastric cancer whose diagnosis, tumor progression, and treatment remain need further investigation [6-9]. Thus, it is urgent to identify novel mediators and the signaling pathways involved in the pathogenesis of AGML, which will provide new potential targets for treatment.…”
Section: Introductionmentioning
confidence: 99%